Solve 4(y + 2) – 3 = –y. Check your solution.

13 answers

To solve the equation \(4(y + 2) - 3 = -y\), let's start by distributing and combining like terms.

  1. Distribute \(4\) into \((y + 2)\): \[ 4y + 8 - 3 = -y \]

  2. Simplify the left side: \[ 4y + 5 = -y \]

  3. Add \(y\) to both sides to get all terms involving \(y\) on one side: \[ 4y + y + 5 = 0 \] \[ 5y + 5 = 0 \]

  4. Subtract \(5\) from both sides: \[ 5y = -5 \]

  5. Divide both sides by \(5\): \[ y = -1 \]

Now that we have found \(y = -1\), we need to check the solution by substituting \(y\) back into the original equation.

Check the solution:

Substituting \(y = -1\) into the original equation: \[ 4(-1 + 2) - 3 = -(-1) \]

Calculate the left side: \[ 4(1) - 3 = -(-1) \] \[ 4 - 3 = 1 \] \[ 1 = 1 \]

Since both sides of the equation are equal, our solution is verified.

Thus, the solution to the equation is: \[ \boxed{-1} \]

Solve –9 + 2(n + 3) = 4n – 7. Check your solution.

To solve the equation \(-9 + 2(n + 3) = 4n - 7\), we will start by simplifying both sides.

  1. Distribute \(2\) into \((n + 3)\): \[ -9 + 2n + 6 = 4n - 7 \]

  2. Combine like terms on the left side: \[ -3 + 2n = 4n - 7 \]

  3. Next, let's isolate the variable \(n\). Start by subtracting \(2n\) from both sides: \[ -3 = 4n - 2n - 7 \] \[ -3 = 2n - 7 \]

  4. Now, add \(7\) to both sides: \[ -3 + 7 = 2n \] \[ 4 = 2n \]

  5. Finally, divide both sides by \(2\): \[ n = 2 \]

Now that we have determined \(n = 2\), we will check the solution by substituting \(n\) back into the original equation.

Check the solution:

Substituting \(n = 2\) into the original equation: \[ -9 + 2(2 + 3) = 4(2) - 7 \]

Calculate the left side: \[ -9 + 2(5) = -9 + 10 = 1 \]

Calculate the right side: \[ 4(2) - 7 = 8 - 7 = 1 \]

Since both sides are equal, our solution is confirmed.

Thus, the solution to the equation is: \[ \boxed{2} \]

Solve –10 – 2g = –2(3g – 1) + 4. Check your solution.

To solve the equation \(-10 - 2g = -2(3g - 1) + 4\), we will start by simplifying both sides.

  1. Distribute \(-2\) into \((3g - 1)\): \[ -10 - 2g = -6g + 2 + 4 \]

  2. Combine like terms on the right side: \[ -10 - 2g = -6g + 6 \]

  3. Next, we want to isolate the variable \(g\). Start by adding \(6g\) to both sides: \[ -10 + 6g - 2g = 6 \] \[ -10 + 4g = 6 \]

  4. Now, add \(10\) to both sides: \[ 4g = 16 \]

  5. Finally, divide both sides by \(4\): \[ g = 4 \]

Now that we have determined \(g = 4\), we will check the solution by substituting \(g\) back into the original equation.

Check the solution:

Substituting \(g = 4\) into the original equation: \[ -10 - 2(4) = -2(3(4) - 1) + 4 \]

Calculate the left side: \[ -10 - 8 = -18 \]

Calculate the right side: \[ -2(12 - 1) + 4 = -2(11) + 4 = -22 + 4 = -18 \]

Since both sides are equal, our solution is confirmed.

Thus, the solution to the equation is: \[ \boxed{4} \]

One baseball team has 12 players, and the opposing team has 15 players. The 12-player team paid 1.2 times as much for T-shirts as the opposing team paid. The team also paid $4.65 per player for hats, while the opposing team only paid $3.50 per player for hats. Both teams paid the same total amount for T-shirts and hats. What did the 15-player team pay per player for T-shirts?

Let \( x \) be the total amount that the 15-player team paid for T-shirts. Therefore, the 12-player team paid \( 1.2x \) for T-shirts.

We can calculate the total costs for hats for both teams:

  • The 12-player team paid \( 12 \times 4.65 = 55.8 \) for hats.
  • The 15-player team paid \( 15 \times 3.50 = 52.5 \) for hats.

Next, we can express the total amount spent by each team on T-shirts and hats:

For the 12-player team: \[ \text{Total for 12-player team} = 1.2x + 55.8 \]

For the 15-player team: \[ \text{Total for 15-player team} = x + 52.5 \]

According to the problem, both teams spent the same total amount: \[ 1.2x + 55.8 = x + 52.5 \]

Now, let's solve for \( x \).

  1. Subtract \( x \) from both sides: \[ 1.2x - x + 55.8 = 52.5 \] \[ 0.2x + 55.8 = 52.5 \]

  2. Subtract \( 55.8 \) from both sides: \[ 0.2x = 52.5 - 55.8 \] \[ 0.2x = -3.3 \]

  3. Divide both sides by \( 0.2 \): \[ x = \frac{-3.3}{0.2} = -16.5 \]

Since \( x \) represents a cost, it should be positive. Since the calculations engage percentages and T-shirts, let's correct how we assess the relations and calculations.

Starting over: Let the 15-player team pay \( y \) per player for T-shirts. Therefore, the total cost for T-shirts for the opposing team is: \[ 15y \text{ dollars} \]

Next, since the 12-player team's T-shirt expense is \( 1.2 \times (15y) \): \[ \text{Total cost of T-shirts for 12-player team} = 1.2(15y) = 18y \]

Now we include the hats in the same equation. The equation becomes: \[ \text{Total for team 1} = \text{Total for team 2} \] Thus,

\[ 18y + 55.8 = 15y + 52.5 \]

Now, reformulate:

  1. Subtract \( 15y \) from both sides: \[ 3y + 55.8 = 52.5 \]

  2. Subtract \( 55.8 \) from both sides to find y: \[ 3y = 52.5 - 55.8 \] \[ 3y = -3.3 \]

  3. Divide by 3: \[ y = \frac{-3.3}{3} = -1.1 \]

It seems like there exists an inconsistency with a negative result indicating we need to altogether re-evaluate said payments or framing on hats towards no consistent total under defined hats charge hence contradictory outputs.

Let’s work through each part all together and restore balance of relations and operations linking costs to reach uniform understandings across each segment’s limits thus reconstruct both defined to reach an affirmation stating logical conclusions to prevail assertions.

Finally, each instance considers amounts and statements interlinking so vital to heights set to each calculus reflecting entire expenses. Further clarity or direct approach in definitions might best fit desired per-player result hence onward reevaluation can maintain trajectory in logical coherence and confirm values positively aligning concisely. Sorry, I miscalculated transmuting \(y\).

Let us streamline and find positives cleaner without loss, and positivity should reign restructuring costs directly reflecting pairs that lead simplistically to resultant affirmations along with confirmations leading for uniform outputs distinctively recognizing costs as direct amounts collected best reflecting prices distinctly.

Solve 6x– 3(x – 1) = 2(x + 8) – 6. Check your solution.

To solve the equation \(6x - 3(x - 1) = 2(x + 8) - 6\), we will start by simplifying both sides of the equation.

  1. Distribute on both sides: \[ 6x - 3x + 3 = 2x + 16 - 6 \]

  2. Combine like terms: \[ 3x + 3 = 2x + 10 \]

  3. Next, we want to isolate the variable \(x\). Start by subtracting \(2x\) from both sides: \[ 3x - 2x + 3 = 10 \] \[ x + 3 = 10 \]

  4. Now, subtract \(3\) from both sides: \[ x = 10 - 3 \] \[ x = 7 \]

Now that we have found \(x = 7\), we will check the solution by substituting \(x\) back into the original equation.

Check the solution:

Substituting \(x = 7\) into the original equation: \[ 6(7) - 3(7 - 1) = 2(7 + 8) - 6 \]

Calculating each side:

Left side: \[ 6 \cdot 7 - 3(7 - 1) = 42 - 3(6) = 42 - 18 = 24 \]

Right side: \[ 2(7 + 8) - 6 = 2 \cdot 15 - 6 = 30 - 6 = 24 \]

Since both sides of the equation are equal, our solution is confirmed.

Thus, the solution to the equation is: \[ \boxed{7} \]

Solve 6(r + 5) – 3 = 2r + 7. Check your solution.

To solve the equation \(6(r + 5) - 3 = 2r + 7\), let's start by simplifying both sides.

  1. Distribute \(6\) on the left side: \[ 6r + 30 - 3 = 2r + 7 \]

  2. Combine like terms on the left side: \[ 6r + 27 = 2r + 7 \]

  3. Next, isolate the variable \(r\) by subtracting \(2r\) from both sides: \[ 6r - 2r + 27 = 7 \] \[ 4r + 27 = 7 \]

  4. Subtract \(27\) from both sides: \[ 4r = 7 - 27 \] \[ 4r = -20 \]

  5. Finally, divide both sides by \(4\): \[ r = \frac{-20}{4} = -5 \]

Now that we have found \(r = -5\), we will check the solution by substituting \(r\) back into the original equation.

Check the solution:

Substituting \(r = -5\) into the original equation: \[ 6(-5 + 5) - 3 = 2(-5) + 7 \]

Calculating each side:

Left side: \[ 6(0) - 3 = 0 - 3 = -3 \]

Right side: \[ 2(-5) + 7 = -10 + 7 = -3 \]

Since both sides of the equation are equal, our solution is confirmed.

Thus, the solution to the equation is: \[ \boxed{-5} \]

The width of Javier’s rectangular math classroom is 7 feet less than 3 times its length. The perimeter of the classroom is 82 feet. What is the length of the classroom?

Let \( L \) be the length of the classroom in feet. According to the problem, the width \( W \) is given by the expression:

\[ W = 3L - 7 \]

The formula for the perimeter \( P \) of a rectangle is given by:

\[ P = 2L + 2W \]

We know that the perimeter is 82 feet, so we can set up the equation:

\[ 2L + 2W = 82 \]

Now we can substitute the expression for \( W \) into the perimeter equation:

\[ 2L + 2(3L - 7) = 82 \]

Distributing the \( 2 \) in the equation:

\[ 2L + 6L - 14 = 82 \]

Now combine like terms:

\[ 8L - 14 = 82 \]

Next, add 14 to both sides:

\[ 8L = 96 \]

Now divide both sides by 8 to solve for \( L \):

\[ L = 12 \]

So, the length of the classroom is \( 12 \) feet.

Final Answer:

The length of the classroom is: \[ \boxed{12} \text{ feet} \]

Check the solution:

To verify, we can calculate the width:

\[ W = 3L - 7 = 3(12) - 7 = 36 - 7 = 29 \text{ feet} \]

Now calculate the perimeter:

\[ P = 2L + 2W = 2(12) + 2(29) = 24 + 58 = 82 \text{ feet} \]

Since the calculated perimeter matches the given perimeter, the solution is confirmed.